2013
DOI: 10.1210/en.2012-2270
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin D Restriction in Pregnant Female Mice Is Associated With Maternal Hypertension and Altered Placental and Fetal Development

Abstract: Epidemiology has linked vitamin D deficiency with preeclampsia in humans. We hypothesized that low vitamin D status in pregnant mice may lead to symptoms of preeclampsia. Female BL6 mice were raised on vitamin D-sufficient or -deficient diets from weeks 4 of age and then mated with vitamin D-sufficient BL6 males at week 8. The resulting pregnant mice were either allowed to deliver pups and monitored for blood pressure (BP) and weight of offspring or euthanized at day 14 or 18 of gestation (E14 or E18) for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 56 publications
(49 reference statements)
3
51
0
1
Order By: Relevance
“…In addition, we propose that BN rats can be a useful model to investigate the molecular and physiological roles of vitamin D during mammalian pregnancy. Recent studies have suggested that vitamin D effects in mammalian pregnancy include the regulation of the immune, endocrine, and cardiovascular systems (2,3,30,31,39) warranting further researc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we propose that BN rats can be a useful model to investigate the molecular and physiological roles of vitamin D during mammalian pregnancy. Recent studies have suggested that vitamin D effects in mammalian pregnancy include the regulation of the immune, endocrine, and cardiovascular systems (2,3,30,31,39) warranting further researc.…”
Section: Discussionmentioning
confidence: 99%
“…No mention was made as to whether maternal vitamin D deficiency led to a reduced conception rate, and no measurements of bone mass or mineralization were performed. The placentas from vitamin D-deficient pregnancies were of identical weight but had smaller diameters, and histological evidence of reduced vascular diameters within the labyrinthine placenta, compared with pregnancies from vitamin D-sufficient mothers (563).…”
Section: Animal Datamentioning
confidence: 93%
“…Nonskeletal outcomes of pregnancy have received little attention in these animal studies, but the recent study of vitamin D-deficient mice found higher systolic and diastolic blood pressure, and upregulation of renal expression of renin and angiotensin II receptor mRNA, compared with vitamin D-sufficient mice (563). These findings support the possibility that vitamin D deficiency may increase the risk of pregnancy-induced hypertension.…”
Section: Animal Datamentioning
confidence: 93%
See 1 more Smart Citation
“…In studies using partially purified uNK cells from first-trimester human pregnancies, treatment with either 25OHD or 1,25(OH) 2 D ex vivo promoted antibacterial and anti-inflammatory responses (Evans et al 2006). In view of the fact that vitamin D deficiency in humans (Bodnar et al 2007b) and mice (Liu et al 2013) has been linked to PET, it is interesting to speculate that uNK cells may play a role in the pathophysiology of this complication of pregnancy. uNK cells appear to play a pivotal role in spiral arteriole remodelling (Robson et al 2012) and the regulation of extravillous trophoblast invasion into decidua basalis and superficial myometrium through the production of local cytokines and chemokines (Lash et al 2010b).…”
Section: Decidual/uterine Nk Cellsmentioning
confidence: 99%